User Perception of a Smartphone App to Promote Physical Activity Through Active Transportation: Inductive Qualitative Content Analysis Within the Smart City Active Mobile Phone Intervention (SCAMPI) Study - Lindqvist, Anna-Karin; Rutberg, Stina; Söderström, Emmie; Ek, Anna; Alexandrou, Christina; Maddison, Ralph; Löf, Marie (JMIR Publications, 2020)
BackgroundPhysical inactivity is globally recognized as a major risk factor for morbidity, particularly the incidence of noncommunicable diseases. Increasing physical activity (PA) is therefore a public health priority. Engaging in active transportation (AT) is a viable approach for promoting daily PA levels. Mobile health interventions enable the promotion of AT to a larger population. The Smart City Active Mobile Phone Intervention (SCAMPI) study was a randomized controlled trial designed to evaluate the ability of a behavior change program delivered via a smartphone app to motivate participants to increase their PA by engaging in AT. ObjectiveThis qualitative study aims to examine the acceptance and user experience of the app promoting AT that was used in the SCAMPI trial (the TRavelVU Plus app). MethodsA total of 17 residents of Stockholm County (13 women; age range 25-61 years) who completed the 3-month app-based behavioral change program (delivered through the TRavelVU Plus app) in the SCAMPI randomized controlled trial during 2018 agreed to participate in a semistructured telephone-based interview. These participants were well representative of the whole intervention group (n=127) in terms of baseline characteristics such as age, sex, and area of residence. The interviews were audiorecorded, transcribed verbatim, and analyzed using an inductive qualitative content analysis. ResultsThe content analysis revealed 2 themes and 4 subcategories. The first theme, "main motivators: monitoring and messages," highlighted that monitoring AT and being able to set weekly goals using the app were the primary motivators reported by study participants. The second theme, "acceptable but modifiable," reflects that the app was well accepted and effectively encouraged many participants to use more AT. Nevertheless, there were functions in the app that require modification. For example, while the semiautomated travel tracking feature was appreciated, participants found it time-consuming and unreliable at times. ConclusionsThis study contributes novel insight into adults' experiences of using a mobile app to promote the use of AT. The results showed that the app was well accepted and that self-monitoring and goal setting were the main motivators to engage in more AT. The semiautomated tracking of AT was appreciated; however, it was also reported to be energy- and time-consuming when it failed to work. Thus, this feature should be improved going forward. Trial RegistrationClinicalTrials.gov NCT03086837; https://clinicaltrials.gov/ct2/show/NCT03086837 International Registered Report Identifier (IRRID)RR2-10.1186/s12889-018-5658-4